Modelling, simulation and control of two-wheeled vehicles - Tanelli, Mara.; Savaresi, Sergio M.; Corno, Mauro, 1970- (Chichester, West Sussex, UK : John Wiley & Sons, 2014)
This book discusses all aspects of two-wheeled vehicles, comprehensively covering the main methods, tools and approaches to address the modelling, simulation and control design issues. It also offers a perspective on the future trends in the field, outlining the challenges and the industrial and academic development scenarios. Extensive reference to real-world problems and experimental tests is also included throughout. --
Part one. Two-Wheeled vehicles modelling and simulation -- part two. Two-wheeled vehicles control and estimation problems.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Motorcycles -- Dynamics; TECHNOLOGY & ENGINEERING -- Engineering (General); Motorcycles -- Dynamics; Electronic books